2017
DOI: 10.1089/mdr.2016.0130
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Mechanisms and Genetic Diversity of Multidrug-ResistantAcinetobacter baumanniiIsolated from a Teaching Hospital in Malaysia

Abstract: Multidrug-resistant (MDR) Acinetobacter baumannii has increasingly emerged as an important nosocomial pathogen. The aim of this study was to determine the resistance profiles and genetic diversity in A. baumannii clinical isolates in a tertiary medical center in Malaysia. The minimum inhibitory concentrations of carbapenems (imipenem and meropenem), cephalosporins (ceftazidime and cefepime), and ciprofloxacin were determined by E-test. PCR and sequencing were carried out for the detection of antibiotic resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…Likewise, A. baumannii isolates collected in 2010 and 2011 from various ward in HSA in the southern state of Johor, displayed resistance rates of 88% for both imipenem and meropenem ( Dhanoa et al, 2015 ). Resistance rates of >70% were also reported for isolates from UKMMC (located south of Kuala Lumpur) in 2010–2011 ( Biglari et al, 2015 , 2017 ) and HSNZ (located in the east coast state of Terengganu) in 2011( Lean et al, 2014 ).…”
Section: Antibiotic Susceptibility Profilesmentioning
confidence: 78%
“…Likewise, A. baumannii isolates collected in 2010 and 2011 from various ward in HSA in the southern state of Johor, displayed resistance rates of 88% for both imipenem and meropenem ( Dhanoa et al, 2015 ). Resistance rates of >70% were also reported for isolates from UKMMC (located south of Kuala Lumpur) in 2010–2011 ( Biglari et al, 2015 , 2017 ) and HSNZ (located in the east coast state of Terengganu) in 2011( Lean et al, 2014 ).…”
Section: Antibiotic Susceptibility Profilesmentioning
confidence: 78%
“…Forty nine Class D (OXA) β-Lactamases have also been described from A. baumannii; 4 of them -(OXA-239, OXA-72, OXA-51, and OXA-253) -were discovered or re-described in the last year [165][166][167][168][169][170].…”
Section: β-Lactamasesmentioning
confidence: 99%
“…This can be related to the several other studies from the continent of Asia, where a high rate of CR is found to be associated with Acinetobacter spp. [24][25][26][27][28][29] Differences in the proportion of MBLs have been documented from all over the world based on surveys of community-acquired and nosocomial infections. However, we have found no meta-analysis study speci cally on Metallo-β-lactamases.…”
Section: Discussionmentioning
confidence: 99%